2018
DOI: 10.3168/jds.2017-14306
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of in vivo bovine blastocyst developmental to gestational Day 15

Abstract: Bovine embryo growth involves a complex interaction between the developing embryo and the growth-promoting potential of the uterine environment. We have previously established links between embryonic factors (embryo stage, embryo gene expression), maternal factors (progesterone, body condition score), and embryonic growth to 8 d after bulk transfer of Day 7 in vitro-produced blastocysts. In this study we recovered blastocysts on Days 7 and 15 after artificial insemination to test the hypothesis that in vivo an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Therefore, the single sample collected at the time of embryo collection in the Day 14 group in the present study may not have been sufficient to observe relationships between progesterone concentrations and conceptus length. In addition, the relationship between progesterone concentrations and length of the conceptus on Day 15 of pregnancy was much weaker when examined in bovine embryos that were developed in vivo following artificial insemination (Shorten et al 2018b) than in embryos produced in vitro and transferred to the uterus on Day 7; this is more consistent with our study, where no correlation was observed on Day 14 following natural mating. Changes in other steroids may also regulate conceptus length.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the single sample collected at the time of embryo collection in the Day 14 group in the present study may not have been sufficient to observe relationships between progesterone concentrations and conceptus length. In addition, the relationship between progesterone concentrations and length of the conceptus on Day 15 of pregnancy was much weaker when examined in bovine embryos that were developed in vivo following artificial insemination (Shorten et al 2018b) than in embryos produced in vitro and transferred to the uterus on Day 7; this is more consistent with our study, where no correlation was observed on Day 14 following natural mating. Changes in other steroids may also regulate conceptus length.…”
Section: Discussionsupporting
confidence: 90%
“…There is also the potential for bacterial toxins arising from the diseased uterus to cause inflammation within the ovary and reduce oocyte competence (Bromfield et al, 2015;Ribeiro et al, 2016). Shorten et al (2018) reported that approximately 65% of inseminated dairy cows had a viable embryo 1 wk after AI (Shorten et al, 2018). The low percentage of pregnant cows 1 wk after AI is perhaps explained by a low-quality oocyte with fertilization failure or poor developmental competence within the oviduct during the first week after AI.…”
Section: Oocyte Qualitymentioning
confidence: 99%
“…IFN-τ is a pregnancy recognition signal that acts on the endometrium to maintain the continuous production of P4 by the ovaries. Additionally, it regulates the genes related to embryonic implantation and growth [11,12]. During pregnancy, the endometrium and embryos of sheep produce prostaglandins including prostaglandin F2α(PGF2α) and prostaglandin E2(PGE2).…”
Section: Introductionmentioning
confidence: 99%